Research on the Relationship Between Digital Transformation and Urban and Rural industrial Integration and Development - Qu, Na; You, Xiaoliang (Journal of Theory and Practice of Social Science, 2024)
This study explores the relationship between digital transformation and the integrated development of urban and rural industries. In the context of economic and social development in the 21st century, the integration of urban and rural development has become an important part of the national strategy, aiming to break the urban-rural dual structure and achieve common prosperity through institutional innovation and technology application. The study found that digital transformation introduces advanced information technology, changes the traditional production management mode, improves efficiency and efficiency, and provides new impetus for the integration of urban and rural industries. This paper analyzes the role mechanism, actual effect, and challenges of digital transformation in urban and rural integration, and predicts the future development trend. The policy proposal emphasizes the deep integration of technology and traditional industries, promoting the development of digital industries, and the two-way flow of urban and rural factors. The forecast shows that the proportion of the primary industry will decline, the innovation capacity of the secondary industry will be enhanced, and the tertiary industry will become the dominant economy. Digital transformation will play a key role in urban-rural integration, promoting the optimization of industrial structure and urban-rural integration.